A study of the explosion parameters of vapor–liquid two-phase JP-10/air mixtures - Liu, Xueling; Wang, Yue; Zhang, Qi (Fuel (Guildford), 2016)
•The SMDs of 19.95 and 34.84μm were studied in Urms∼3.5–7m/s.•The evaporation rate for smaller particles is larger than for larger particles.•The peak pressure and temperature for smaller SMDs is larger than for larger SMDs.•The concentration of Pmax is greater than Tmax regardless of particle size.•LFL and Pmax will be subject to corresponding vapor-phase concentration. In this study, we investigated the explosion parameters of vapor–liquid two-phase JP-10 (C10H16, tricycle [5.2.1.02, 6] decane)/air mixtures, and reported new experimental data obtained at various conditions. Two sets of vapor–liquid two-phase JP-10/air mixtures at different fuel concentrations, with Sauter mean diameters (SMDs) of 20μm and 35μm, respectively, were examined. Their explosion temperature, pressure and lower flammability limits were measured and analyzed in the current study.